Multicollinearity in regression analysis: effects, detection and methods of minimising / Azmi Abdul Latiff - Abdul Latiff, Azmi (1982)
The general purpose of this paper is to examine the effects of multicollinearity in regression analysis, explore ways of detecting and present the methods of minimising these effects.